2012
DOI: 10.4314/sajas.v42i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of body weight in South African Angora kids and young goats

Abstract: The data used for this study consisted of 27 485 kid records, the progeny of 599 sires and 10 077 dams, and were collected on the 2000-to 2009-born kids of 11 Angora goat studs. Variance and covariance components and ratios pertaining to direct additive genetic variation, maternal additive genetic variation, maternal permanent environmental variation, and the relationship between direct and maternal effects for birth weight (BW; kg), weaning weight (WW; kg) and body weight at 8, 12 and 16 months (W8, W12 and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
11
2
Order By: Relevance
“…The heritability for ABW was estimated as 0.42±0.17 which was higher than 0.38 as estimated by Borg et al (2009) in Western sheep but lower than 0.58±0.03 as reported by Snyman (2012) in Angora goats.…”
Section: Genetic Parameterscontrasting
confidence: 64%
“…The heritability for ABW was estimated as 0.42±0.17 which was higher than 0.38 as estimated by Borg et al (2009) in Western sheep but lower than 0.58±0.03 as reported by Snyman (2012) in Angora goats.…”
Section: Genetic Parameterscontrasting
confidence: 64%
“…Low to moderate estimates of genetic correlation between the birth and weaning weight were documented by some researchers [12][13][14][15][16][17][18][19][20][21][22][23]. Low phenotypic correlation as found in present study between the two traits were also reported by different researchers [12,17,20,24].…”
Section: Birth Weight and Weaning Weightsupporting
confidence: 74%
“…These fitness traits show a slow selection response to conventional selection and incorporation of marker assisted selection (MAS) could result in faster genetic gains. After validation, the putative QTL identified in this study could be used to manipulate early growth and due to a strong positive genetic correlation, also yearling weight in Angora goats (Snyman, 2012). Additional research would however first be required to decrease the confidence interval ranges significantly in order to determine the precise locations of the QTL.…”
Section: Discussionmentioning
confidence: 94%
“…Although inter-age genetic correlations for body weight are strongly positive, this correlation decreases as time between measurements increases, indicating separate QTL that govern different growth stages (Hadjipavlou & Bishop, 2008). Snyman (2012) reported that no increase in direct or maternal birth weight was found over the past ten years in South African Angora goat stud herds making use of the current SI. This emphasises the need to identify chromosomal segments of interest for birth and weaning weight in order to improve survivability and reproduction efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation